EVALUATING GRAMMATICAL COMPETENCE IN KURDISH EFL JUNIOR STUDENTS’ WRITINGS AT THE ENGLISH DEPARTMENT, COLLEGE OF LANGUAGES, UNIVERSITY OF DUHOK - SULAIMAN , MOHAMMED SALIH A.; MOHAMMED, HAJIN GHAZI (Journal of Duhok University, 2020)
ABSTRACT While writing is as important as the other three skills (reading, listening, and speaking), most students have a big problem with it. This could be the fault of the teaching methods/techniques or the materials used in classrooms. This paper aims at evaluating the grammatical competence in Kurdish EFL students' writings. The aim is to point out those areas of grammar that need more focus and determine which teaching techniques and materials are most suitable for helping students in developing their writing skills. The researcher first evaluated students’ grammatical competence using a test, and then evaluated their ability to apply grammatical rules in their written essays. The data from the grammar test and the essay test were analyzed using the SPSS (Statistical Package for the Social Sciences) Software. The participants were 93 students at the English Department of Duhok University. The results indicated that the students had struggled most with prepositions in the grammar exam and had the least trouble with pronouns. However, regarding the essay test, majority of the students made errors concerning articles, and the least number of errors were made regarding coordinators. It was, however, found that the students avoided the use of complex grammatical structures in their writings, and it could be because there is not enough practice in the classroom.